2017
DOI: 10.1016/j.molmet.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-4 inhibitor treatment induces a greater increase in plasma levels of bioactive GIP than GLP-1 in non-diabetic subjects

Abstract: ObjectiveGlucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) possess multiple bioactive isoforms that are rendered non-insulinotropic by the enzyme dipeptidyl peptidase-4 (DPP-4). Recently, some ELISA kits have been developed to specifically measure “active” GIP and GLP-1, but it is unclear if these kits can accurately quantify all bioactive forms. Therefore, it remains uncertain to what extent treatment with a DPP-4 inhibitor boosts levels of biologically active GIP and GLP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
(40 reference statements)
5
19
1
1
Order By: Relevance
“…Identified as a novel adipokine in AT [129], DPP4 is strongly expressed on the apical surfaces of the polarized epithelium of various organs such as lung and liver, and increased DPP4 results in failures to resolve inflammation and chronic subclinical activation of the immune system [128]. Interestingly, DPP4 is upregulated in obesity, especially in the insulin resistance state [129,130]. Inhibition of DPP4 prevented fibrosis in obese white AT [131].…”
Section: Sars-cov-2 Receptors Proteases Adipose Tissue and Obesitymentioning
confidence: 99%
“…Identified as a novel adipokine in AT [129], DPP4 is strongly expressed on the apical surfaces of the polarized epithelium of various organs such as lung and liver, and increased DPP4 results in failures to resolve inflammation and chronic subclinical activation of the immune system [128]. Interestingly, DPP4 is upregulated in obesity, especially in the insulin resistance state [129,130]. Inhibition of DPP4 prevented fibrosis in obese white AT [131].…”
Section: Sars-cov-2 Receptors Proteases Adipose Tissue and Obesitymentioning
confidence: 99%
“…Plasma total ghrelin and total GIP concentrations were measured by Elisa kits from Millipore [18]. The intra-assay CV for GIP and ghrelin were 1.8% and 3.6%.…”
Section: Hormone Assaysmentioning
confidence: 99%
“…In the present study, in a unilateral 6-OHDA MFB lesion rat model of PD, we demonstrated that GIP treatment stabilized apomorphine-induced rotational behavior and showed positive changes in open field locomotor tests, as well as some anxiety-like behaviors. This was achieved at a plasma active GIP concentration that is achievable in humans by use of a DPP-4 inhibitor [ 24 , 25 ]. To our knowledge, our study is the first to evaluate the action of GIP in a 6-OHDA PD animal model and adds to the growing literature that GIP may be of value as a treatment strategy for PD [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 50% GIP dose reduction resulted in an 80% decline in total, as well as active GIP plasma levels. Importantly, these concentrations are achievable in humans following the use of DPP-4 inhibitors [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%